Kultuurdiversiteit en ontwikkelingsbehoeftes in Suid-Afrika: Implikasies vir maatskaplikewerkopleiding - Strydom, H (Social Work/Maatskaplike Werk, 2000)
This article fo cuses on cultural diversity of the South African population and the important role that the social worker plays as a practician and as a teacher of social work plays. Emphasis is placed on the demands of the current practice and the equipping of the social worker. Certain curriculum requirements that are of importance in the plarining of social work training are also discussed. The developmental research and utilisation model (DR&U) of Thomas (1981 , 1984 and 1985) has bee n used as research method. Postal questionnaires were utilised as data gathering method for the research project. Questionnaires have been sent to the South African universities, the Hugenote College and practising social workers of the North West Province. The developmental needs of the South African society and how universities can specifically meet these needs were also discussed in this article.